TYRE PRESSURE MONITORING SYSTEM - OMAR, EDZUAN (Universiti Teknologi Petronas, 2005)
Maintaining the correct tyre pressure for a vehicle is the variable in how much load its tyres can safely carry. The correct pressure will carry the weight without a problem. Too little tyre pressure will eventually cause catastrophic tyre failure. This project requires student to study the existing system ofTPMS and ifpossible to come up with depth research on how to design the system from scratch. This project is the initial background work for the development of a miniature pressure sensor and controller unit for TPMS. The main purpose ofthese systems is to warn the driver if their tyres are losing air pressure, leaving the tyres under inflated and dangerous. The systems attach a pressure sensor together with transmitter to the vehicle's wheel inside the tyre's air chamber. The final objective ofthe continuous project is to design a circuit consists ofpressure sensor, microcontroller (PIC), transmitter and receiver. The pressure sensor used is amicroelectronic device. This system will read apressure inside the tyre and transmit itto the receiver which can produce the output (display). This report represents approaches to the scope of developing the MEMS pressure sensor which used inTPMS. The methodology divided by two; TPMS methodology and MEMS pressure sensor methodology. For the TPMS methodology, input from pressure sensor is required before a transmitter unit transmits the data to a receiver and displays the value of the pressure. For the MEMS methodology, it was divided into mechanical and electrical design elements. Mostly the related information is collected from reference books and from internet. As for the conclusion tyre pressure monitoring system is an interesting area of focus and opens up a new field of technology and creative thinking.